Auditory-Motor Control of Vocal Production during Divided Attention: Behavioral and ERP Correlates - Liu, Ying; Fan, Hao; Li, Jingting; Jones, Jeffery A.; Liu, Peng; Zhang, Baofeng; Liu, Hanjun (Frontiers in Neuroscience, 2018)
When people hear unexpected perturbations in auditory feedback, they produce rapid compensatory adjustments of their vocal behavior. Recent evidence has shown enhanced vocal compensations and cortical event-related potentials (ERPs) in response to attended pitch feedback perturbations, suggesting that this reflex-like behavior is influenced by selective attention. Less is known, however, about auditory-motor integration for voice control during divided attention. The present cross-modal study investigated the behavioral and ERP correlates of auditory feedback control of vocal pitch production during divided attention. During the production of sustained vowels, thirty-two young adults were instructed to simultaneously attend to both pitch feedback perturbations they heard and flashing red lights they saw. The presentation rate of the visual stimuli was varied to produce a low, intermediate, and high attentional load. The behavioral results showed that the low-load condition elicited significantly smaller vocal compensations for pitch perturbations than the intermediate-load and high-load conditions. As well, the cortical processing of vocal pitch feedback was also modulated as a function of divided attention. When compared to the low-load and intermediate-load conditions, the high-load condition elicited significantly larger N1 responses and smaller P2 responses to pitch perturbations. These findings provide the first neurobehavioral evidence that divided attention can modulate auditory feedback control of vocal pitch production.